Workload effect on Adversity Quotient through Emotional Quotient as Intervening Variable in Palu City Supermarket - Lina Mahardiana; Saharuddin Kaseng; Yobert Kornelius (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2022)
This study aims to examine the workload of employees that affect the adversity quotient either directly or indirectly through the emotional quotient as an intervening variable. The research participants were 108 supermarket employees in Palu City who were taken randomly from 26 supermarket outlets which were taken according to their proportions. The results obtained indicate that the effect of workload on the adversity quotient can be weakened if there is an emotional quotient that affects the workload and adversity quotient. In conclusion, this study provides a different perspective on the adversity quotient in the work environment. Another scientific addition is that the emotional quotient can be an adversity quotient reinforcement for individuals to survive the workload. It is possible that other quotients can strengthen the role of the adversity quotient in the world of work.